The role of meteorological and hydrological uncertainties in the performance of optimal water allocation approaches†. (15th January 2019) - Anvari, S.; Kim, J.H.; Moghaddasi, M.
Abstract: Efficient reservoir operation and irrigation scheduling are important for the mitigation of water shortages in Iran. For more accuracy, the hydrological and meteorological uncertainties associated with reservoirs and farm levels should be considered. The major contribution of the current paper is to evaluate the uncertainties of evapotranspiration (ET) and inflow, and the issue of constant/variable agricultural demand (CAD/VAD) for optimal irrigation scheduling and reservoir operation. Some optimization approaches were employed and compared during a drought episode in the Zayandeh‐Rud agricultural system. Approaches include: (i) DP‐CAD: dynamic programming (DP), considering CAD and no inflow uncertainty; (ii) SSDP‐CAD: sampling stochastic DP (SSDP) with CAD and inflow uncertainty; (iii) LP‐NLP‐VAD: implementing linear (LP) and non‐linear programming (NLP) modelling for crop types, growing stages, and irrigation systems under deterministic conditions; (iv) SDP‐NLP‐VAD: similar to the third approach, but considers ET uncertainties using a stochastic DP (SDP) rather than an LP model, and uses stochastic crop yield functions in the NLP formulation. DP‐CAD and SDP‐NLP‐VAD were the simplest and most complicated modelling processes, respectively. SDP‐NLP‐VAD was the most time‐consuming to reach a steady state and a global optimal solution. The LP‐NLP‐VAD and SDP‐NLP‐VAD approaches, which account for variability in crop water requirements, conservatively consider water shortages and reservoir release. © 2019 John Wiley & Sons, Ltd. Résumé: L'efficacité de l'exploitation des réservoirs et la planification de l'irrigation sont importantes pour atténuer les pénuries d'eau en Iran. Pour plus de précision, les incertitudes hydrologiques et météorologiques associées aux niveaux des réservoirs et des exploitations agricoles devraient être prises en compte. La contribution principale du présent papier consiste à évaluer les incertitudes de l'évapotranspiration (ET) et du flux entrant, la question de la demande agricole constante/variable (CAD/VAD) pour optimiser la planification de l'irrigation et l'exploitation du réservoir. Certaines approches d'optimisation ont été utilisées et comparées au cours d'un épisode de sécheresse du système agricole Zayandeh‐Rud. Les approches incluent: (i) DP‐CAD: programmation dynamique (DP), prenant en compte la CAD et l'absence d'incertitude liée au flux entrant; (ii) SSDP‐CAD: DP stochastique d'échantillonnage (SSDP) avec CAD et incertitude d'entrée; (iii) LP‐NLP‐VAD: implémentation de la modélisation par programmation linéaire (LP) et non linéaire (NLP) pour les types de cultures, les stades de croissance et les systèmes d'irrigation dans des conditions déterministes; (iv) SDP‐NLP‐VAD: similaire à la troisième approche, mais considère les incertitudes ET en utilisant un DP stochastique (SDP) plutôt qu'un modèle LP, et utilise des fonctions stochastiques du rendement des cultures dans la formulation de la NLP. Les processus de modélisation DP‐CAD et SDP‐NLP‐VAD étaient respectivement les plus simples et les plus compliqués. SDP‐NLP‐VAD était la solution la plus longue à atteindre un état stable et une solution globale optimale. Les approches LP‐NLP‐VAD et SDP‐NLP‐VAD, qui tiennent compte de la variabilité des besoins en eau des cultures, prennent en compte de manière conservatrice les pénuries d'eau et la libération des réservoirs. © 2019 John Wiley & Sons, Ltd.